2011
DOI: 10.1007/s00213-011-2345-x
|View full text |Cite
|
Sign up to set email alerts
|

Contingent negative variation as a dopaminergic biomarker: evidence from dose-related effects of methylphenidate

Abstract: RationaleThe basal ganglia play an important role in motor control, which is dependent on dopaminergic input. Preparation of a motor response has been associated with dopamine release in the basal ganglia, and response readiness may therefore serve as a pharmacodynamic marker of dopamine activity.MethodsWe measured response readiness using the amplitude of the contingent negative variation (CNV), a slow negative shift in the electroencephalogram. The CNV is evoked in a paradigm in which a warning stimulus (S1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 41 publications
5
38
0
Order By: Relevance
“…This is consistent with the notion that MPH speeds up response time in healthy volunteers (Elliott et al, 1997), reflecting response-readiness enhancing effects (Linssen et al, 2011).…”
Section: Speed Of Processingsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the notion that MPH speeds up response time in healthy volunteers (Elliott et al, 1997), reflecting response-readiness enhancing effects (Linssen et al, 2011).…”
Section: Speed Of Processingsupporting
confidence: 91%
“…Another component assessed in the studies listed in Table 4 was the Contingent Negative Variation (CNV). MPH was observed to enhance CNV amplitude, reflecting increased response readiness (Coons et al, 1981;Linssen et al, 2011). Event-related desynchronization, measured during a visual search task, was not affected by MPH (Oken et al, 1995).…”
Section: Imaging Studies On Cognitive Performance Under the Influencementioning
confidence: 88%
“…In a recent study, methylphenidate was found to increase CNV-amplitudes (Linssen et al, 2011). Most of the children with ADHD in the present study received treatment with methylphenidate.…”
Section: Methodological Issuessupporting
confidence: 51%
“…Patient research and studies with healthy individuals have indicated that the CNV might be related to the dopaminergic system (e.g., Amabile et al, 1986; Gerschlager et al, 1999; Linssen et al, 2011). Consequently, the observed interaction between task difficulty and reward in this component appears to be consistent with the results of the previous fMRI study of Krebs et al (2012) showing a very similar interaction pattern in the dopaminergic midbrain with highest activation levels in respond to cues that predicted both reward and high difficulty.…”
Section: Discussionmentioning
confidence: 99%